Reducing Unplanned Extubations in a Pediatric Intensive Care Unit: A Systematic Approach - Bonnie R. Rachman; Robin Watson; Norline Woods; Richard B. Mink (Hindawi Limited, 2009)
Objective. To prospectively determine the rate of unplanned extubations and contributing factors and determine whether a targeted intervention program would be successful in decreasing the rate of unplanned extubations. Design. Prospective, observational study. Setting. A 10-bed Pediatric Intensive Care Unit (PICU). Patients. All intubated pediatric patients during two time periods: September 1, 2000-March 31, 2001 and November 1, 2001-April 30, 2002. Interventions. After determining the rate and causes of unplanned extubation, a program was developed consisting of education and a formalized endotracheal tube taping policy. Data were then collected after implementation of the program. Measurements and Main Results. Prior to the implementation of the program, there were 10 (14.7%) unplanned extubations for a rate of 6.4 unplanned extubations per 100 ventilated days. Of the ten unplanned extubations, reintubation was required in 2 (20%). Inadequate sedation, poor taping, and improper position of the endotracheal tube were the items most frequently cited as causing an unplanned extubation. Following the program, there were two (3.4%) unplanned extubations for 1.0 unplanned extubations per 100 ventilated days. Neither patient required reintubation. There were no significant differences (𝑃>.05) in age, weight, endotracheal tube size, or duration of intubation in the two time periods. However, there was a significant decrease in both the number (𝑃=.03) and the rate (𝑃=.04) of unplanned extubations after the implementation of the quality improvement program. Conclusions. The rate of unplanned extubation in a PICU can be decreased with a quality improvement program that targets the institution's specific needs.